Proposed upgrading works of tourism centre for George Town World Heritage Office at 116&118, Lebuh Acheh, George Town, Penang / Khairunnisa Shariffuddin - Shariffuddin, Khairunnisa (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect of interior design that had been learnt from basic to the final presentation on the proposed design. The chosen project is proposed upgrading works of tourism centre for George Town World Heritage Office at 116 & 118, Acheen Street, George Town, Penang. The project aim is to upgrade the space and design enabling the tourists and local communities to know about George Town heritage area. The research objectives are to identify tourism information’s spatial design requirement and create more welcoming environment, to identify the facilities and furniture suitable for office and tourism centre and redesign the image for information center and mini gallery. All of the data were collected using the primary research methodology such as site measured, interview with the client and site observation. There are also secondary research data gathered from magazines, internet and journal. I hope that the report would benefit the students, lecturers, researchers and local communities.